2020
DOI: 10.2147/oajsm.s244512
|View full text |Cite
|
Sign up to set email alerts
|

<p>Small-Sided Games are More Enjoyable Than High-Intensity Interval Training of Similar Exercise Intensity in Soccer</p>

Abstract: Introduction: High-intensity interval training (HIIT) and small-sided games (SSG) have been applied and tested for athletes in order to enhance the soccer performance. For this reason, this experimental study aimed to compare the effects of SSGs and HIIT on power, physiological responses and perceived enjoyment. Materials and Methods: Sixteen youth soccer players (age, 17.5±0.6 years, mean±standard deviation; height, 178.2±6.4 cm; body mass, 70.4±5.4 kg; body fat, 10.6±0.8%) completed one session each of HIIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
(57 reference statements)
7
35
1
1
Order By: Relevance
“…When asked to attribute pleasure scores to exercises used in their training routine, Olympic judo athletes reported high values for judo-specific exercises, which were their main training activities ( Franchini and Takito, 2014 ). Additionally, the results of the present study are consistent with those of Selmi et al (2020) which reported that high-intensity training leads to positive affective responses when using sport-specific exercise modalities (i.e., small-sided games in soccer players) compared with a non-specific training modality. Therefore, it is likely that sport-specific exercises are preferred by and more motivating for athletes, resulting in lower stress scores compared with non-sport-specific exercises.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When asked to attribute pleasure scores to exercises used in their training routine, Olympic judo athletes reported high values for judo-specific exercises, which were their main training activities ( Franchini and Takito, 2014 ). Additionally, the results of the present study are consistent with those of Selmi et al (2020) which reported that high-intensity training leads to positive affective responses when using sport-specific exercise modalities (i.e., small-sided games in soccer players) compared with a non-specific training modality. Therefore, it is likely that sport-specific exercises are preferred by and more motivating for athletes, resulting in lower stress scores compared with non-sport-specific exercises.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, performing technical actions and specific combat skills produced better emotional responses compared with running training in Olympic judo athletes (Franchini and Takito, 2014). Furthermore, a recent study in soccer players demonstrated that exercise based on technical actions (e.g., small sided games) was perceived to be more enjoyable than general athletic training (Selmi et al, 2020). Altogether, physical enjoyment appears to reflect attitude, sport preference, and intrinsic motivation and varies according to exercise modality.…”
Section: S5mentioning
confidence: 97%
“…Considering each training modality separately, physical enjoyment was largely unrelated to well-being indices, RPE, and TQR for all groups during both training periods suggesting that these variables minimally contribute to altered physical enjoyment during judo training modalities. Rather, physical enjoyment may be more closely related to positive emotional reactions and motivation during training [ 15 , 32 , 33 , 34 , 35 ]. The nuances of physical enjoyment during different training phases among combat sports athletes warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Future analysis should consider interconnected factors accompanying sport-specific to non-specific training that may influence objective and subjective measures of training load. For instance, recent analysis of high-intensity interval training via running vs. small-sided games demonstrated athlete's report greater enjoyment during small-sided games (Selmi et al, 2020 ). This leads to the potential that while similar physiological stress may occur between two sessions, the player's perception of the stress may vary according to the dynamics of the player experience.…”
Section: Discussionmentioning
confidence: 99%